2016
DOI: 10.1177/0003489415624701
|View full text |Cite
|
Sign up to set email alerts
|

Device Life of Two Generations of Provox Voice Prostheses

Abstract: Device longevity was greater for Provox 2 over Provox Vega. These results will facilitate the design of prospective studies to assess reasons for variations in device life between patients and device types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Specific tissues pertaining to a voice prosthesis include details pertaining to the length of voice prosthesis, expense, diameter, type of retention collar, method of insertion, need for follow-up care, and the patient's ability to care for the prosthesis. For the past several decades, a voice prosthetic device has become the gold standard of voice rehabilitation for a majority of the laryngectomy patients, with the exception of the odd patient who has acquired good esophageal speech or for whom an external device is the only practical method of voice production [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific tissues pertaining to a voice prosthesis include details pertaining to the length of voice prosthesis, expense, diameter, type of retention collar, method of insertion, need for follow-up care, and the patient's ability to care for the prosthesis. For the past several decades, a voice prosthetic device has become the gold standard of voice rehabilitation for a majority of the laryngectomy patients, with the exception of the odd patient who has acquired good esophageal speech or for whom an external device is the only practical method of voice production [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…This is also objectively reflected as the better voice parameters, i.e., fundamental frequency, shimmer, jitter, words per minute, and better Not received maximum phonation time for the lung-powered speech. Voice rehabilitation after laryngectomy has in fact been revolutionized by use of TEP with voice prosthesis; many studies over the years have in fact reported its superiority to esophageal speech/electrolarynx speech [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results mirror clinical experience, such as the reported device lifetimes of specialty prostheses or the similar device lifetimes of the Provox 2 and its successor the Provox Vega prosteses. 33 Two other voice prosthesis, such as the Blom Singer classic prosthesis and the Newvox prosthesis could not be included in the study: the white color of the valve flap of the Blom Singer classic prostheses provided insufficient color contrast to perform simple optical biofilm quantification; and the Newvox prosthesis made of polyurethane could not be provided by the manufacturer in sufficient numbers.…”
Section: Discussionmentioning
confidence: 99%